ANALISIS VARIABEL-VARIABEL YANG MEMPENGARUHI KINERJA BADAN USAHA KONSULTAN PERENCANAAN BANGUNAN DI KOTA PALEMBANG - Anisa, Ariska; Firdaus, Firdaus (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2025)
Several factors can influence company performance, namely effectiveness and efficiency, authority, and creative thought initiatives within the company. These important factors are related to the influence of human resources, K3 management and company finances on company performance. From the data from the questionnaire, there were 25 respondents from the planning consultant business entity at INKINDO Palembang, with qualifications in Human Resources, K3 (Occupational Safety and Health), and Financial Reports. Judging from the analysis of each variable that influences the performance of planning consultant business entities in the city of Palembang, the conclusion is that based on the t-test, it is found that the Human Resources (HR) variable has a positive and significant effect on company performance at INKINDO Planning Consultants in the city Palembang. The K3 variable (Occupational Safety and Health) has a positive and significant effect on company performance at INKINDO Planning Consultants in the city of Palembang. The Company Financial Report variable has a positive and significant effect on company performance at INKINDO Planning Consultants in the city of Palembang. Based on the results of the calculated F test, the simultaneous or joint influence of Human Resources (HR), K3 (Occupational Safety and Health) and Company Financial Reports on the Performance of Business Entities at INKINDO Planning Consultants in Palembang City was obtained.Keywords: INKINDO Palembang, Planning Consultant, SPSS 25